EFEKTIVITAS MANAJEMEN PEMASARAN PADA PEMBIAYAAN WARUNG MIKRO : STUDI KASUS PADA BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU BEKASI TIMUR - Laksmitawuri, Hendry Candra; ., Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The title of this article is, "'Effectiveness of Marketing Management at Warung Micro Financing: A Case Study of Bank Syariab Mandiri Sub Branch OfBce Bekasi Timur". The conclusion of this article that the marketing management applied by Warung Micro BSMKCPBast Bekasi is by door to door, distribution ofb/vchurvs, an assessment directly to the market-the market, participate in events held by various parties as well as establishing a good relationship to customers has been granted financing facilities. In addition, based on observations of researchers, for the current marketing management applied by Warung Micro BSM appropriate theories that have been expressed by some experts* but the realization that there is not yet able to achieve the target set by the BSM allegedly due to lack of maximum employment marketing Warung Micro